Emotional responding in NSSI: examinations of appraisals of positive and negative emotional stimuli, with and without acute stress - Tatnell, R.; Hasking, Penelope; Lipp, Ottmar; Boyes, Mark; Dawkins, Jessica (Routledge, 2018)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. Non-suicidal self-injury (NSSI) is commonly used by young adults to regulate emotional responses. Yet, experimental examination of how people who self-injure appraise and respond to emotional stimuli is limited. We examined appraisals of, and responses to, emotive images in young adults who did and did not self-injure, and assessed whether these were impacted by exposure to a stressor. Study 1 (N?=?51) examined whether participants differed in their appraisals of emotional images. Study 2 (N?=?78) assessed whether appraisals of images changed after exposure to the Trier Social Stress Test. Ratings of emotional valence and arousal were collected in both studies; skin conductance was measured as an indicator of physiological arousal in Study 2. In Study 1 participants reporting NSSI rated positively valenced images as less pleasant than participants not reporting NSSI. In Study 2, after acute stress, participants reporting NSSI displayed dampened physiological reactions to positive images whereas participants who did not self-injure displayed heightened physiological reactions to these and rated them as more pleasant. Individuals who self-injure seem less able to engage in strategic mood repair after exposure to stress compared to people who do not self-injure.